2023
DOI: 10.3389/fnut.2023.1014010
|View full text |Cite
|
Sign up to set email alerts
|

Functional foods and dietary supplements in the management of non-alcoholic fatty liver disease: A systematic review and meta-analysis

Abstract: ObjectiveIn this systematic review and meta-analysis, we aimed to clarify the overall effects of functional foods and dietary supplements in non-alcoholic fatty liver disease (NAFLD) patients.MethodsRandomized controlled trials (RCTs) published in PubMed, ISI Web of Science, Cochrane library, and Embase from January 1, 2000 to January 31, 2022 were systematically searched to assess the effects of functional foods and dietary supplements in patients with NAFLD. The primary outcomes were liver-related measures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“… 20 Several studies also revealed the feasibility of L. acidophilus supplementation against NAFLD and NASH in human patients and in mouse models. 21 , 22 Here, we for the first time discovered the anti-tumourigenic effect of L. acidophilus against NAFLD-HCC in mice, suggesting the potential of probiotic administration against the development of liver malignancy.…”
Section: Discussionmentioning
confidence: 76%
“… 20 Several studies also revealed the feasibility of L. acidophilus supplementation against NAFLD and NASH in human patients and in mouse models. 21 , 22 Here, we for the first time discovered the anti-tumourigenic effect of L. acidophilus against NAFLD-HCC in mice, suggesting the potential of probiotic administration against the development of liver malignancy.…”
Section: Discussionmentioning
confidence: 76%
“…In a non-randomized, propensity score-adjusted study, a daily intake of 800 IU of vitamin E was associated with significant reductions in total mortality and hepatic decompensation in patients with MASH-induced bridging fibrosis and cirrhosis, both in diabetic and non-diabetic individuals ( 36 ). Moreover, vitamin E has been effective in lowering AST and ALT levels in adult patients with MAFLD ( 91 ). It inhibits oxidative stress, which reduces de novo lipogenesis (DNL) and intrahepatic triglyceride (IHTG) accumulation, thereby disrupting the cycle between oxidative stress and the MAFLD process ( 92 ).…”
Section: Vitamins and Mafldmentioning
confidence: 99%
“…Diet and exercise therapy are recommended to prevent the onset and progression of NASH. Nevertheless, few medical studies have demonstrated the effect of food on the onset and progression of NASH [8]. Sake lees are by-products of the process of sake production.…”
Section: Introductionmentioning
confidence: 99%